High Power Yb Fiber Laser With Picosecond Bursts and the Quasi-Synchronously Pumping for Efficient Midinfrared Laser Generation in Optical Parametric Oscillator - Peipei Jiang; Chengzhi Hu; Tao Chen; Pinghui Wu; Bo Wu; Ruhua Wen; Yonghang Shen (IEEE Photonics Journal, 2016)
A fiber laser-pumped high-power burst-mode-operated picosecond mid-infrared (IR) laser at 3.8 $μ\text{m}$ is reported. A gain-switched distributed Bragg reflector laser diode with a pulse repetition rate (PRR) of 138 MHz and pulse duration around 200 ps was applied as the seed laser of a master oscillator power amplifier (MOPA)-structured Yb fiber laser. The PRR of the MOPA was increased to about 1.1 GHz through a pulse multiplier consisting of four cascaded 2 $×$ 2 fiber couplers. A fiber-pigtailed acousto-optic modulator was used to carve the pulse train into pulse bursts so that the peak power of the final linearly polarized fiber laser output could be optimized by adjusting the duty cycle of the pulse bursts correspondingly. The output of the fiber laser was directed to pump a periodically poled magnesium-oxide-doped lithium niobate-based optical parametric oscillator through the quasi-synchronized pump scheme. Efficient parametric conversion was realized with a maximum average power output of 7.3 W at 3.8 $μ\text{m}$ under pump power of 45 W at 1.064 $μ\text{m}$ with pump-to-idler conversion efficiency exceeding 16%.